PENERAPAN PENDIDIKAN KARAKTER DI KALANGAN MAHASISWA - Susanti, Rosa (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
Education system in Indonesia is often in the spotlight, not only through print and electronic media, but also through cyberspace. Education in Indonesia is often tarnished by rampant incidents that are not well done by the students, ranging from engaging Drugs, promiscuity, fighting, until the murder. The problem occurs not only due to the lack of control of the parents, but also from school. Therefore, today a lot of changes in our education system, one of them are Character Education. The character education teaches habitual ways of thinking and behavior that help learners to live and work together with families, communities, and countries and help them to make decisions that can be accounted for. Because the character is not formed instantaneously, but must be trained seriously, continuous and proportionate in order to achieve the ideal form of character.Copyright © 2013 by Al-Talim All right reservedDOI: 10.15548/jt.v20i3.46